A new species of Bernardia (Euphorbiaceae) from the Chapada Diamantina, Bahia State, Brazil - Carrión, Juan F.; Cordeiro, Inês; Amorim, André Márcio (Phytotaxa, 2017)
This work describes and illustrates Bernardia hamadryadica, from the Chapada Diamantina, in northeastern Brazil. The new species is distinguished from the other species of the genus by the combination of the following characters: shrubby habit; young leaves and inflorescences usually produced on short shoots; membranaceous leaf laminas less than 6 cm long, with disk-shaped, slightly prominent glands on the abaxial surface; spiciform staminate inflorescences up to 1 cm long; entire style branches; and indumentum of simple trichomes.